Previne Brasil na visão dos gestores municipais de saúde da macrorregião Norte do Ceará: um estudo por métodos mistos. - Linhares, Auxiliadora Elayne Parente (2024)
Primary Health Care, mainly the Family Health Strategy, was one of the strategies to offer health services to the population, focusing on the people and families who live in a specific locality. This type of care makes it possible to achieve important results, such as reducing maternal and child mortality and other preventable diseases. For this reason, the PHC financing and evaluation program, Previne Brasil, was launched in 2019. Proposed by Ministerial Ordinance No. 2,979 of November 12, 2019, it has three dimensions: weighted capitation, incentives for strategic actions and programs, and payment for performance, as the best way to finance the actions needed to provide care to the Brazilian population. This research aimed to analyze the vision of municipal health managers in the Northern Macroregion of the State of Ceará on the results of Previne Brasil in the management of Primary Health Care in their municipalities. This was a mixed study with the participation of 12 municipal health managers from the Northern Macroregion of the state of Ceará. The data was collected and analyzed through a search on the federal government's E-Gestor website of the scores for the four-month periods in 2121, 2022 and 2023, in which 20 municipalities emerged to be evaluated. The semi-structured interviews were then analyzed using Bardin's Content Analysis, and three categories of analysis emerged (SUS, Previne Brasil and Managers; Previne Brasil Indicators; Evaluation, Management and Previne Brasil). Through these categories, it was possible to identify that Previne Brasil funding has led to changes in local public administration, mainly with the aim of ensuring the transfer of resources to Primary Health Care. Although the municipalities have made efforts to implement new health facilities and encourage the workers directly involved, achieving the targets set by the program has proved to be a major challenge. As a result, many municipalities were unable to meet the required indicators, which had a direct impact on the total amount of funding passed on, which was lower than expected. This situation made it difficult to guarantee health care that fully complied with the fundamental principles of the Unified Health System.